2019
DOI: 10.1002/ange.201908210
|View full text |Cite
|
Sign up to set email alerts
|

Dual Graphitic‐N Doping in a Six‐Membered C‐Ring of Graphene‐Analogous Particles Enables an Efficient Electrocatalyst for the Hydrogen Evolution Reaction

Abstract: Graphene-based materials still exhibit poor electrocatalytic activities for the hydrogen evolution reaction (HER) although they are considered to be the most promising electrocatalysts.W ef abricated ag raphene-analogous material displaying exceptional activity towards the HER under acidic conditions with an overpotential (57 mV at 10 mA cm À2 )a nd Tafel slope (44.6 mV dec À1 )s uperior to previously reported graphene-based materials,and even comparable to the state-ofthe art Pt/C catalyst. X-raya bsorption n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Even though pristine graphene exhibits inert activity as electrocatalyst, it is possible to tune its electronic structures and correspondingly reactivities by introducing heteroatoms. [ 10‐12 ] For example, nitrogen dopants (generally can be classified as pyridinic N, pyrrolic N and graphitic N according to their configurations as shown in Figure 1a) can tweak the electronic and electrochemical properties of graphene sheet via tailoring the electronic density of C atoms, changing them into active sites. [ 13 ] Moreover, Bao et al .…”
Section: Introductionmentioning
confidence: 99%
“…Even though pristine graphene exhibits inert activity as electrocatalyst, it is possible to tune its electronic structures and correspondingly reactivities by introducing heteroatoms. [ 10‐12 ] For example, nitrogen dopants (generally can be classified as pyridinic N, pyrrolic N and graphitic N according to their configurations as shown in Figure 1a) can tweak the electronic and electrochemical properties of graphene sheet via tailoring the electronic density of C atoms, changing them into active sites. [ 13 ] Moreover, Bao et al .…”
Section: Introductionmentioning
confidence: 99%
“…N-Zn-C materials retain the structural features of parent ZIF-8 particles. ZIF-8 particles are consisted of a mass of graphene-analogous particles, 33 which can provide rich active sites for implanting heteroatoms. Phosphorus has the same number of valence electrons as nitride [34][35] and a much greater radius than carbon; hence, P-doping in carbon drives local structural distortion in carbon hexagonal framework and enlarges the basal plane spacing, which could facilitate Na-ion transport.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Qiao et al reported a nonmetal iodine single-atom electrocatalyst with robust structural stability and exceptional electrocatalytic activity for HER in an alkaline solution [ 31 ]. Lin et al group-fabricated a graphene-analogous material, in which the active carbon atom is displaying unusual activity toward the HER under acidic conditions [ 32 ]. Works in this direction are still at an early stage; there is still a significant challenge in understanding the catalytic reaction mechanism in monoatomic nonmetal catalysts.…”
Section: Introductionmentioning
confidence: 99%